Sustainability Management at the Federal University of Mato Grosso do Sul - Brazil: Integrating Institutional Projects with the SDGs - Costa, Joao Vitor; de Carvalho, Leonardo Chaves; Turine, Marcelo Augusto Santos; Itavo, Camila Celeste Brandao Ferreira (Journal of Sustainability Perspectives, 2024)
The Federal University of Mato Grosso do Sul (UFMS) is the largest educational institution in the Midwest of Brazil, with its quality in teaching, research, extension, management, and infrastructure recognized at national and international levels. In 2023, the university received the highest rating in the institutional assessment conducted by the Ministry of Education (MEC), the government body responsible for promoting quality education in the country, and for the first time, ranked in the top 100 global in the UI GreenMetric World University Ranking. UFMS was considered the 74th most sustainable university out of 1,183 institutions evaluated, and the 5th in the country. The university implements various good practices aligned with each of the Sustainable Development Goals (SDGs) of the United Nations (UN) 2030 Agenda. The aim of this work is to present some of these practices, with an emphasis on incorporating the SDGs into the university's teaching, research, and extension projects. In a quantitative and descriptive analysis, from 2018 to 2023, there have been over 20,000 projects registered at UFMS with more than 45,000 SDGs indicated. It is hoped that this study can inspire other institutions regarding the importance of meeting the SDGs.